PENGARUH PENGGUNAAN PENDEKATAN PARTISIPATIF TERHADAP HASIL BELAJAR FISIKA - Santi Septiana Zarita; Cut Liliiza Yusra; Hery Wiharja. MS (Jurnal Bionatural, 2024)
This study aims to determine the effect of the participatory approach on Physics learning outcomes. The research aims to explore the impact of using a participatory approach on students' learning achievements. The population of this study consists of all eighth-grade students from SMP Negeri 14 Banda Aceh, which includes 5 classes with a total of 135 students. The sample in this study was selected using purposive sampling technique, involving 2 classes: class VIII/B with 29 students as the experimental group and class VIII/A with 28 students as the control group. Data collection was carried out using a testing technique, and data analysis was performed using a T-test. Based on the data analysis at a 5% significance level (α = 0.05) and degrees of freedom (df) = 51, the t-value obtained was t-hitung = 2.248 and the t-table value was t-tabel = 1.68, leading to the acceptance of the alternative hypothesis (Ha). Based on the research findings, it can be concluded that the use of a participatory approach can improve students' learning outcomes. The results of this study can serve as one of the many pieces of information to enhance students' learning achievements.